2022
DOI: 10.1002/pssb.202100512
|View full text |Cite
|
Sign up to set email alerts
|

The Origin and Formation Mechanism of an Inclined Line‐like Defect in 4H‐SiC Epilayers

Abstract: The origin and the formation mechanism of a surface morphological defect in 4H‐SiC epilayers are reported. The defect appears on the surface of an epilayer as an inclined line‐like feature at an angle of ±80° to the step‐flow direction . The defect is confirmed to originate from a threading screw dislocation intersecting the surface and its orientation is controlled by the sign of the Burgers vector of the dislocation. The defect forms through the interaction of local spiral growth associated with threading sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…[ 29 ] Increasing the C/Si ratio eliminates SSBs but leads to the formation of ILL surface morphological defects (Figure 5b–e). [ 25 ] Notably, two different orientations of the ILL defects can be observed, with angles of +80 and −80 degrees to the step‐flow direction. Most importantly, no such defects are observed when growth is performed using CH4$\left(\text{CH}\right)_{4}$ as a C source even with a high C/Si ratio.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 29 ] Increasing the C/Si ratio eliminates SSBs but leads to the formation of ILL surface morphological defects (Figure 5b–e). [ 25 ] Notably, two different orientations of the ILL defects can be observed, with angles of +80 and −80 degrees to the step‐flow direction. Most importantly, no such defects are observed when growth is performed using CH4$\left(\text{CH}\right)_{4}$ as a C source even with a high C/Si ratio.…”
Section: Resultsmentioning
confidence: 99%
“…The origin and formation mechanism of ILL surface morphological defects on 4 H‐SiC epitaxial layers are discussed in detail in ref. [25]. There we have demonstrated that TSDs present in the substrate are responsible for the formation of such defects.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The main destructive defects are instant surface dislocation (BPD) defects and stacking faults (SF), which are likely to continuously increase the on-resistance of bipolar devices [25][26][27][28][29][30][31][32][33][34][35]. Surface defects, such as dump, scratch, particle, downfall (DF), triangle (TD), comet and carrot defects, are typically detrimental and easily observable, and often lead to device failure [36][37][38][39][40][41][42]. Therefore, one of the main challenges in 4H-SiC epitaxial growth is to decrease the defect density of the epitaxial layer.…”
Section: Methodsmentioning
confidence: 99%
“…The main destructive defects are instant surface dislocation (BPD) defects and stacking faults (SF), which are likely to continuously increase the on-resistance of bipolar devices [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Surface defects, such as dump, scratch, particle, downfall (DF), triangle (TD), comet and carrot defects, are typically detrimental and easily observable, and often lead to device failure [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%